A companion to the study of Virgil - Horsfall, Nicholas. (Brill's Companions in Classical Studies Online I, ISBN: 9789004219274., 2000)
This book is not yet another introduction to Virgil's poetry. The editor and three contributors offer a guide to the key problems and to the most intelligent discussions. They do not hesitate to point out what we do not know, and where more work needs to be done. Apart from ample discussion of the poems and the main issues they raise, the book offers chapters on the life of Virgil, his style, and his influence on late Latin epic.